Młodzież NEET we fragmentarycznej rzeczywistości społecznej – próba charakterystyki - Stawska , Marta (Studia Edukacyjne, 2022)
The following article is devoted to a social phenomenon that is increasingly becoming a point of interest to many research communities. It is a NEET youth Not in Employment, Education or Training), who simultaneously meet three conditions: they are not studying, not working and not training in formal education system. On the basis of literature on the subject and available data, the article discusses the theoretical aspects of the NEET phenomenon and fragmented social reality. In addition, statistics and methods of reintegration to facilitate re-entry into the labor market are presented.